The Role of a Confined Space on the Reactivity and Emission Properties of Copper(I) Clusters - Prasetyanto, Eko Adi; Atoini, Youssef; Donato, Loic; Hsu, Chien-Wei; De Cola, Luisa (Frontiers in Chemistry, 2022)
Metal clusters have gained a lot of interest for their remarkable photoluminescence and catalytic properties. However, a major drawback of such materials is their poor stability in air and humidity conditions. Herein we describe a versatile method to synthesize luminescent Cu(I) clusters inside the pores of zeolites, using a sublimation technique, by the help of high vacuum and high temperature. The porous materials play an important role as a protecting media against the undesirable and easy oxidation of Cu(I). The obtained clusters show a very interesting luminescence and their reactivity can be triggered by insertion in the pores of organic monodentate ligands such as pyridine or triphenylphosphine. The coordinating ligands can lead to the formation of Cu(I) complexes with completely different emission properties. In the case of pyridine, the final compound was characterized and identified as a cubane like structure. A thermochromism effect is also observed, featuring for instance a hypsochromic effect for a phosphine derivative at 77K. The stability of the encapsulated systems in zeolites is rather enthralling: they are stable and emissive even after several months in air.